When Healthy Habits Turn Harmful: A Medical Perspective on Exercise Addiction - Hądzlik, Izabela; Wojtyła, Klaudia; Barg, Marta (Quality in Sport, 2024)
Behavioural addictions, also known as non-substance-related addictions, encompass a range of compulsive behaviours that closely mirror substance use disorders in their effects on the brain's reward system and the individual's daily life. These addictions include, but are not limited to, gambling disorder, internet gaming disorder, compulsive shopping, and the focus of this review - exercise addiction. Exercise addiction is characterized by an intense, uncontrollable urge to engage in physical activity, despite potential negative consequences. Unlike substance use disorders, exercise addiction often remains underrecognized, overshadowed by the widespread promotion of regular physical activity as a healthy lifestyle choice. This review aims to offer a comprehensive overview of exercise addiction, covering its psychological origin and characteristics, diagnostic criteria, co-occurrence with other psychiatric disorders, epidemiology among athletes and management strategies.